1974
DOI: 10.3109/00016347409157754
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assay of HCG, HCT and HCS in Molar Pregnancy

Abstract: Ahstrrrci. The authors studied the secretion patterns of three chorionic polypeptide hormones (HCG. HCT and HCS) and the clinical usefulness of the assay of these hormones in patients with hydatidiform mole, by means of systematic serial estimation. in comparison with the secretion patterns in normal pregnancy. The serum levels of HCG and HCT in molar pregnancy were usually higher than in normal pregnancy but HCS levels were below the lower limit of normal pregnancy of the same gestational age. This dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Recently, we have detected large amounts of HCT in the serum of patients with molar pregnancies by radioimmunoassay using 131-HCT and anti-HCT serum (6), and suggested that the HCT level was a useful indicator in the treatment of chorionic neoplasm (13).…”
mentioning
confidence: 99%
“…Recently, we have detected large amounts of HCT in the serum of patients with molar pregnancies by radioimmunoassay using 131-HCT and anti-HCT serum (6), and suggested that the HCT level was a useful indicator in the treatment of chorionic neoplasm (13).…”
mentioning
confidence: 99%